Stationary axially symmetric solutions in Brans-Dicke theory - (:unkn) unknown (AMER PHYSICAL SOC, 2015)
Stationary, axially symmetric Brans-Dicke-Maxwell solutions are reexamined in the framework of the Brans-Dicke (BD) theory. We see that, employing a particular parametrization of the standard axially symmetric metric simplifies the procedure of obtaining the Ernst equations for axially symmetric electrovacuum spacetimes for this theory. This analysis also permits us to construct a two parameter extension in both Jordan and Einstein frames of an old solution generating technique frequently used to construct axially symmetric solutions for BD theory from a seed solution of general relativity. As applications of this technique, several known and new solutions are constructed including a general axially symmetric BD-Maxwell solution of Plebanski-Demianski with vanishing cosmological constant, i.e., the Kinnersley solution and general magnetized Kerr-Newman-type solutions. Some physical properties and the circular motion of test particles for a particular subclass of Kinnersley solution, i.e., a Kerr-Newman-NUT-type solution for BD theory, are also investigated in some detail.
Keywords: BLACK-HOLES; GENERAL-RELATIVITY; FORMULATION; GEOMETRY; ORBITS; FIELDS